A compact solvent extraction based 99Mo/99mTc generator for hospital radiopharmacy. (January 2019) - Chattopadhyay, Sankha; Saha Das, Sujata; Barua, Luna; Pal, Asit Kumar; Kumar, Umesh; Madhusmita,; Alam, Md. Nayer; Hudait, Arup Kumar; Banerjee, Sharmila
Abstract: A compact and portable 99 Mo- 99 m Tc generator based on solvent-extraction, mimic to the conventional 99 Mo- 99 m Tc alumina column generator is much-needed commodity for use in hospital radiopharmacy setup. The present study includes the development of a portable, simple and low cost 99 Mo/ 99 m Tc-generator based on MEK solvent extraction technique to obtain a very high concentration of no-carrier added (nca) 99 m Tc solution, where low specific activity 99 Mo source is obtained through 98 Mo(n, γ) 99 Mo reaction in a research reactor. The unit is intended for operation under the conditions of medical radiological laboratories. Technical trials showed that the mean time of preparation of sodium [ 99m Tc] pertechnetate radiopharmaceutical did not exceed 15 min. The quality and yield of 99 m Tc-pertechnetate is upto the mark for formulation of radiopharmaceuticals.